Adsorption of organic molecules on graphene and fluorographene: An unresolved discrepancy between experiment and theory. Issue 10 (3rd February 2021) - Iribarne, Federico; Denis, Pablo A.
Abstract: Herein, we studied the adsorption of 15 organic and three polar molecules onto pristine and fluorinated graphene. Two levels of fluorination were selected, CF fluorographene for which all carbon atoms are fluorinated and C4F fluorinated graphene, which maximizes the number of Clar sextets. Five different density functionals were employed: M06‐L, M06‐2X, PBE‐D2 and PBE‐D3BJ. In contrast with recent experimental investigations, we found that the adsorption energies for organic molecules onto perfect graphene are significantly lower than those determined for fluorographene. This situation is exacerbated when enthalpic and free energy corrections are included. However, a different scenario was found for polar molecules such as H2 O, H2 O2 and HF. Partial fluorination following a C4F pattern leads to significantly lower adsorption energies for these three molecules, and the superhydrophilicity of C4F is maintained after thermodynamic corrections are included. In fact, even the removal of a single fluorine atom results in a dramatic change in the adsorption energy of water on fluorographene. We discuss the performance of the density functionals assayed and the importance of using finite and infinite models. This work demonstrates that it is possible to adjust the adsorption energy of a given polar molecule onto graphene by controlling the fluorination level and in doing so, that partially fluorinated graphene models may open new avenues for the separation of molecules with different polarity. Abstract : A discrepancy between experiment and theory! Calculations indicate that organic molecules are more strongly adsorbed on graphene as compared with fluorographene, but experimental investigations point to fluorographene despite its lower surface area!